Internalisasi Nilai Kejujuran Melalui Kegiatan Ekstrakurikuler Berbasis Pendekatan Social-Emotional Learning (SEL) Dalam Penguatan Pendidikan Karakter - Moh. Ulum; Moh. Nur Arianto (Lembaga Riset dan Inovasi Almatani, 2026)
The cultivation of honesty values in madrasah has not been optimal, as character education still emphasizes cognitive aspects while extracurricular activities are not systematically designed using a Social-Emotional Learning (SEL) approach. This study aims to analyze the implementation of extracurricular activities, the integration of the five core SEL competencies (self-awareness, self-management, social awareness, relationship skills, and responsible decision-making), and their effectiveness in internalizing honesty values at MA Nurul Wahid Al Wahyuni. This research employed a qualitative approach with a descriptive-evaluative design, with data collected through participatory observation, in-depth interviews with the principal, extracurricular supervisors, and 12 students, as well as documentation. Data were analyzed using the interactive model of Miles and Huberman, with validity ensured through source and technique triangulation. The results indicate that extracurricular activities such as scouting and banjari implicitly incorporate SEL elements through social interaction and positive habituation; the five SEL competencies are integrated as a bridge between moral knowing, moral feeling, and moral action; and these activities are fairly effective in fostering honesty through direct experience, although their implementation still depends on the initiative of supervisors. The novelty of this study lies in the formulation of a conceptual model integrating SEL into extracurricular design as an operational pathway for internalizing honesty values in madrasah.